Global Increase in Circular RNA Levels in Myotonic Dystrophy - Czubak, Karol; Taylor, Katarzyna; Piasecka, Agnieszka; Sobczak, Krzysztof; Kozlowska, Katarzyna; Philips, Anna; Sedehizadeh, Saam; Brook, J. David; Wojciechowska, Marzena; Kozlowski, Piotr (Frontiers in Genetics, 2019)
Splicing aberrations induced as a consequence of the sequestration of MBNL splicing factors on the DMPK transcript, which contains expanded CUG repeats, present a major pathomechanism of myotonic dystrophy type 1 (DM1). As MBNLs may also be important factors involved in the biogenesis of circular RNAs (circRNAs), we hypothesized that the level of circRNAs would be decreased in DM1. To test this hypothesis, we selected twenty well-validated circRNAs and analyzed their levels in several experimental systems (e.g., cell lines, DM muscle tissues, and a mouse model of DM1) using droplet digital PCR assays. We also explored the global level of circRNAs using two RNA-Seq datasets of DM1 muscle samples. Contrary to our original hypothesis, our results consistently showed a global increase in circRNA levels in DM1 and we identified numerous circRNAs that were increased in DM1. We also identified many genes (including muscle-specific genes) giving rise to numerous (>10) circRNAs. Thus, this study is the first to show an increase in global circRNA levels in DM1. We also provided preliminary results showing the association of circRNA level with muscle weakness and alternative splicing changes that are biomarkers of DM1 severity.